Seznanjenost žensk s samopregledovanjem zunanjega spolovila - Marolt, Nina (Obzornik zdravstvene nege, 2009)
Introduction: Vulvar carcinoma is a rare disease with an incidence rate of only 4 % of all female genital neoplasms. It is prevalent in women over 50 years of age. The most common histological type of vulvar cancer is planocellular carcinoma. Its aetiology is unknown and affects primarily older,overweight, nulliparous women with early menopause, smokers and promiscuous women as well as those suffering from chronic vulvitis. Aim: The research was designed to determine the level of knowledge of the vulvar cancer, its risk factors and early symptoms along with the percentage of women performing vulvar self-inspection. Methods: A questionnaire was developed and used for the given purpose. Included in the study were 60 women visiting the gynaecological out-patient centre at Šlajmerjeva 2, Ljubljana in January and February, 2008. Results: Most of the respondents belonged to 31-50 years of age group, 72 % of whom had graduated from high school. The majority of the interviewees had heard of the risk factors for developing the disease but their knowledge of these factors, however, was insufficient. 45 % of the women were not aware that smoking is also one of the risk factors. The information about vulvar cancer was obtained through the media (27 %), or provided by their gynaecologist (17 %) and nurses (only 9 %). 62 % of the women perform vulvar self-examination, 17 % on a monthly basis and the rest only occasionally, 30 % using a mirror. Discussion and conclusion: Results ofthe study show that the knowledge on vulvar self-examination is inadequate and that women need more information about the vulvar cancer, its risk factors and the significance of regular self-examination of the vulva, using a mirror.
Keywords: diagnostika; rak (medicina); samopregledovanje; therapy; vulvektomija; woman; zdravljenje; zunanje spolovilo; ženske